Sajak Dalam Khotbah Ali Bin Abi Talib (Analisis Retoris dan Spiritualis) - Wa Erwita; Haniah (Lentera Jurnal, 2026)
This article aims to analyze the patterns and forms of poetry in the sermons of Ali ibn Abi Talib, particularly in the Sermon of Al-Gharra’ (Sermon No. 83) from Nahj al-Balaghah, as well as to examine its rhetorical functions and spiritual dimensions in the context of Islamic da’wah. This study employs a qualitative library research method with a rhetorical and spiritual analytical approach. The primary data source is Nahj al-Balaghah, compiled by Sayyid al-Radhi, supplemented by classical and contemporary works on balaghah and rhetoric in Islam. Data were collected through documentation and a systematic literature review, then analyzed in three stages: identification of the types of Poetry, analysis of rhetorical functions, and interpretation of spiritual meanings. The research findings reveal three types of Poetry in the sermons of Ali ibn Abi Talib mutharraf, mutawazi, and murashsha each serving distinct rhetorical functions: reinforcing moral warnings (inzar), creating rhythmic appeal (taswiq), and enhancing spiritual awareness. The use of Poetry is not merely an aesthetic device but a rhetorical strategy for conveying profound spiritual values concerning divine sovereignty, human accountability, and ethical civilization in Islam.